1999
DOI: 10.1073/pnas.96.5.1904
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietins 3 and 4: Diverging gene counterparts in mice and humans

Abstract: The angiopoietins have recently joined the members of the vascular endothelial growth factor family as the only known growth factors largely specific for vascular endothelium. The angiopoietins include a naturally occurring agonist, angiopoietin-1, as well as a naturally occurring antagonist, angiopoietin-2, both of which act by means of the Tie2 receptor. We now report our attempts to use homologybased cloning approaches to identify new members of the angiopoietin family. These efforts have led to the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
286
3
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(299 citation statements)
references
References 18 publications
2
286
3
8
Order By: Relevance
“…15 Angiopoietins (Ang1-4) are ligands for the tyrosine kinase receptor Tie2. [16][17][18] Ang1 activates Tie2 signaling pathways and promotes the recruitment of pericytes and smooth muscle cells to the developing vessels 16,19 and contributes to tumor dissemination and metastasis. 20 Ang2, on the contrary, functions in a context-dependent manner as an antagonist promoting either blood vessel growth or regression depending on the levels of other growth factors, such as VEGF-A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Angiopoietins (Ang1-4) are ligands for the tyrosine kinase receptor Tie2. [16][17][18] Ang1 activates Tie2 signaling pathways and promotes the recruitment of pericytes and smooth muscle cells to the developing vessels 16,19 and contributes to tumor dissemination and metastasis. 20 Ang2, on the contrary, functions in a context-dependent manner as an antagonist promoting either blood vessel growth or regression depending on the levels of other growth factors, such as VEGF-A.…”
Section: Introductionmentioning
confidence: 99%
“…22 Ang2 is also required for normal lymphatic vessel formation. 23 Mouse Ang3 and human Ang4 are interspecies orthologues, 18 whose functions have not yet been clarified. The function of Tie1 is less well characterized than that of Tie2 because of the lack of its own specific ligands, although it has been recently shown that the Tie1 receptor can interact with Tie2 and signal as a heterodimeric complex.…”
Section: Introductionmentioning
confidence: 99%
“…To date there are four known angiopoietins, which all bind to the Tie-2 receptor, mediating vessel stabilization signals, whereas the Tie-1 receptor has so far no known ligand (Figure 2) Maisonpierre et al, 1997;Kim et al, 1999;Valenzuela et al, 1999). The phenotypes of Tie-2 and Ang-1 de®cient mice suggest a role for this ligand ± receptor system in maintaining communication between endothelial cells and the surrounding mesenchyme, in order to establish stable cellular and biochemical interactions between endothelial cells and pericytes/ smooth muscle cells (Dumont et al, 1994;Puri et al, 1995;Suri et al, 1997).…”
Section: Angiopoietinsmentioning
confidence: 99%
“…The Angiopoietin family of growth factors is comprised of four family members that bind to the Tie2 tyrosine kinase receptor with different outcomes. Angiopoietin-1 (Ang1), the main ligand for Tie2 [18,19], and -4 [20] are agonistic ligands, whereas Angiopoietin-2 (Ang2) and -3 can serve as antagonistic ligands [20,21]. Although Ang1 does not stimulate proliferation of endothelial cells [18], in vitro Ang1 can induce endothelial migration [22], tubule formation [23] and sprouting [24,25], and survival from a variety of apoptotic insults [26][27][28][29], suggesting that Ang1 can be a potent pro-angiogenic factor.…”
Section: Angiopoietins and Tie2mentioning
confidence: 99%